2006
DOI: 10.1093/jn/136.10.2475
|View full text |Cite
|
Sign up to set email alerts
|

Glyceroneogenesis Is Reduced and Glucose Uptake Is Increased in Adipose Tissue from Cafeteria Diet–Fed Rats Independently of Tissue Sympathetic Innervation

Abstract: The pathways of glycerol-3-P (G3P) generation were examined in retroperitoneal (RETRO) and epididymal (EPI) adipose tissues from rats fed a cafeteria diet for 3 wk. The cafeteria diet induced marked increases in body fat mass and in the plasma levels of insulin and triacylglycerol (TAG). RETRO and EPI from cafeteria diet-fed rats had increased rates of norepinephrine turnover (143 and 60%, respectively) and of de novo fatty acid (FA) synthesis (58 and 98%), compared with controls fed a balanced commercial diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
6
23
0
7
Order By: Relevance
“…In addition, hypertension of CD-fed SHR increased further above controls, while the impaired insulin resistance also deteriorated further, as reflected by the slightly enhanced glucose and doubled insulin levels. Previous studies have demonstrated plasma glucose to be not or only marginally altered by various different high-calorie diets with insulin being usually doubled [27,33,45,47,49] . Thus, our findings on CD-fed SHR are within the range given in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypertension of CD-fed SHR increased further above controls, while the impaired insulin resistance also deteriorated further, as reflected by the slightly enhanced glucose and doubled insulin levels. Previous studies have demonstrated plasma glucose to be not or only marginally altered by various different high-calorie diets with insulin being usually doubled [27,33,45,47,49] . Thus, our findings on CD-fed SHR are within the range given in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Because fasting causes an increase in pyruvate incorporation into G-3-P as well as an increase in PEPCK-C activity, glyceroneogenesis has been implicated in the enhanced TG-FA cycling associated with fasting. Furthermore, a diet high in carbohydrate decreases the activity of PEPCK-C in white adipose tissue (10); these changes are largely due to alterations in gene transcription (11). We hypothesized that after 48 h fast PEPCK-C activity would be increased, resulting in enhanced glyceroneogenesis in the adipose tissue, whereas a high carbohydrate, lipogenic diet would decrease PEPCK-C activity and lower flux over this pathway.…”
mentioning
confidence: 99%
“…CAF refers to free access to different foods of the human diet, palatable and high energetic, inducing obesity due to an excessive intake of energy . Earlier studies by our group showed that CAF induces body adiposity, nonalcoholic fatty liver disease and increases de novo fatty acid synthesis in the liver and in white and brown adipose tissues . CAF also increases serum insulin levels and activates the sympathetic flux to white and brown adipose tissue, but not to the liver …”
Section: Introductionmentioning
confidence: 82%
“…The use of this rapid and potent model for obesity induction may be useful in detecting new pathways for preventive or therapeutic interventions to treat human obesity . This diet delivers increased amounts of carbohydrates and leads to a buildup in body fat, white adipose tissue, and TAG …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation